Physical Activity Status and Influencing Factors among Office Workers in China: A Cross-sectional Study - Wang, Xinghua (Technium Social Sciences Journal, 2025)
Physical inactivity among office workers has become a significant public health concern in China, making it crucial to understand the current status and influencing factors of physical activity among this population for developing effective interventions. This cross-sectional study investigated the physical activity status and identified influencing factors among 1,248 office workers in Liaoning Province, China, using the International Physical Activity Questionnaire (IPAQ) to assess physical activity levels and focus group discussions with 58 participants to explore influencing factors. Data were analyzed using descriptive statistics and thematic analysis. Results showed that the mean daily sitting time in weekdays was 8.3 hours (SD = 2.1), with 38.2% of participants sitting more than 9 hours daily, and only 32.4% met WHO physical activity recommendations. Focus group analysis revealed multiple barriers including time constraints from work demands, environmental factors such as harsh winters and limited facilities, cultural factors related to traditional work culture, and economic considerations including the cost of facilities, with individual motivation, workplace culture, and accessibility emerging as key themes influencing physical activity behavior. The findings demonstrate that office workers have low physical activity levels and prolonged sedentary behavior, indicating that interventions targeting individual motivation, workplace environment, and organizational support are needed to promote physical activity in this population.